FEATURES OF EXPRESSIVE FEMALE SPEECH IN THE POLITICAL DISCOURSE OF SPAIN AND LATIN AMERICA - Natalia Petlyuchenko; Valeria Chernyakova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
This paper represents a multimodal analysis of the paraverbal (prosodic and gesture) features of expressive female political speech in Latin America and Spain. The language corpus consisted of public speeches delivered by Spanish-speaking female politicians Eva Peron, Christina de Kirchner and Manuela Carmena. The article includes an overview of theoretical approaches to female speech studies and follows current trends in modern sociolinguistics, which, on the one hand, accumulate the classical techniques (particularly, experimental methods) of studying the gender-related specifics of the oral female speech based on social standing, age and professional affiliation, and, on the other hand, reflect the latest approaches to the contrastive analysis of socio-political discourse in the "Spanish-Speaking World" (Spain and Latin America). This contributes to the study of gender, speech effect and comparative issues. We offer an audiovisual analysis method for studying voice and kinetic means of the expressive speech of female politicians in Spain and Latin America. This allows determining the ethno-specific correlates of expressiveness in a speech of female politicians at the verbal and paraverbal levels and building an updated model of female political expressiveness based on the integrity of its verbal and paraverbal categories.